A forest of your own : the Pacific Northwest handbook of ecological forestry - Hanson, Kirk; Zuckerman, Seth (Skipstone, 2024)
"A Forest of Your Own is based on the principle of ecological forestry-recognizing that a forest is not a "wood factory," but rather a whole system that has been entrusted to human stewards. In this comprehensive how-to manual, authors Kirk Hanson and Seth Zuckerman explore all aspects of forest ownership-everything from how to evaluate a piece of land before you buy it through creating-and implementing--long-term management plans that may include establishing and protecting new stands of trees, harvesting mushrooms and medicinal plants as well as wood, and protecting your forests far into the future"--